Evolution of physiological responses and fatigue analysis in padel matches according to match outcome and playing position - Marcos-Rivero, B.; Yanci, J.; Granados, C.; Picabea, J. M.; Ascondo, J. (Sensors, 2025)
Padel is a doubles racket sport played on an enclosed court, characterised by intermittent high-intensity efforts, frequent directional changes, and short recovery periods. This study aimed to analyse the evolution of physiological responses and neuromuscular fatigue in amateur padel players according to playing position (Right Side [RS] vs. Left Side [LS]) and match outcome (Win or Lose). A total of 52 padel players (35.6 ± 11.6 years) participated, competing in 13 matches. The mean match duration was 57.2 ± 15.7 min, with an average of 152.0 ± 40.4 points per match. Physiological variables were recorded during each set, and neuromuscular variables (countermovement jump [CMJ] and handgrip strength) were assessed before the match and after each set. No significant differences in physiological load were found between winners and losers or between RS and LS positions. However, differences in handgrip strength were observed at T1 (p < 0.05, d = -0.72) and T2 (p < 0.05, d = -0.59) (post-set testing), with LS players showing higher grip strength. Regarding the progression of physiological responses across the different sets, a progressive increase in cardiovascular load was observed within each subgroup, with significant differences across sets (set 1, set 2, and set 3) in several variables, including HRpeak, HRavg, zone 1, zone 2, zone 3, and TRIMPEdwards. No performance decline was observed in CMJ or handgrip strength in any of the groups analysed. These findings suggest that physiological responses increase throughout a match, particularly in the final sets, but no signs of neuromuscular fatigue (CMJ and handgrip) were observed, regardless of match outcome or playing position. These results highlight the need to include high-intensity scenarios and role-specific strategies in training to address the progressive physiological demands and positional differences in match play.